The Semantic Web: Semantics and Big Data 10th International Conference, ESWC 2013, Montpellier, France, May 26-30, 2013. Proceedings - Cimiano, Philipp; Corcho, Oscar; Presutti, Valentina; Hollink, Laura; Rudolph, Sebastian (Information Systems and Applications, incl. Internet/Web, and HCI ;, 2013)
This book constitutes the refereed proceedings of the 10th Extended Semantic Web Conference, ESWC 2013, held in Montpellier, France, in May 2013. The 42 revised full papers presented together with three invited talks were carefully reviewed and selected from 162 submissions. They are organized in tracks on ontologies; linked open data; semantic data management; mobile Web, sensors and semantic streams; reasoning; natural language processing and information retrieval; machine learning; social Web and Web science; cognition and semantic Web; and in-use and industrial tracks. The book also includes 17 PhD papers presented at the PhD Symposium.